Algebra in superextensions of inverse semigroups - Banakh, T.; Gavrylkiv, V. (Algebra and Discrete Mathematics, 2012)
We find necessary and sufficient conditions on an (inverse) semigroup X under which its semigroups of maximal linked systems λ(X), filters φ(X), linked upfamilies N₂(X), and upfamilies υ(X) are inverse.